The Routledge companion to the life and legacy of Guru Hargobind: sovereignty, militancy, and empowerment of the Sikh Panth - Singh, Pashaura (Routledge, 2025)
"This companion studies the Life and Legacy of Guru Hargobind (1590-1644), the sixth Guru of the Sikh tradition. It highlights the complex nature of Sikh society and culture in the historical and socio-economic context of Mughal India. The book reconstructs the life of Guru Hargobind by exploring the 'divine presence' in history and memory. It addresses the questions of why and how militancy became explicit during Guru Hargobind's spiritual reign, and examines the growth of the Sikh community's self-consciousness, separatism, and militancy as an integral part of the process of empowerment of the Sikh Panth. A unique contribution, this book provides a multidisciplinary paradigm in the reconstruction of Guru Hargobind's life and legacy. It will be indispensable for students of Sikh studies, religious studies, history, sociology of religion, anthropology, material culture, literary and textual studies, politics, militancy, and South Asian studies"--